Donepezil to lecanemab-advancements in targeted therapy of Alzheimer’s disease so far - Khanam, Fouqia Mahnaz (International Journal of Advances in Medicine, 2023)
Alzheimer's disease (AD) first identified as Alois Alzheimer in 1907, is a slowly progressing dementia that affects cognition, behaviour and functional status. There is no cure for AD since precise pathophysiological mechanisms underlying it is not completely known. Drugs may temporarily reduce the symptoms associated with disorder, but condition is ultimately fatal. Objective of treatment of AD is to reduce behaviour issues associated with memory loss and improve cognition. Single acetylcholinesterase inhibitors donepezil and galantamine, as well as the dual AChE and butyrylcholinesterase (BuChE) inhibitor rivastigmine, are now utilized in treatment of AD. Cholinesterase inhibitors have shown dose-dependent impact on cognition and functional activities in clinical trials. Memantine NMDA receptor antagonist is used to minimize neurotoxicity that's suspected to contribute to conditions like Alzheimer's and other neurodegenerative disorders. Estrogen administration post menopause can result in modulation of synaptogenesis, enhanced cerebral blood flow, mediation of crucial neurotransmitters and hormones, protection against apoptosis. Aducanumab is 1st disease modifying drug and monoclonal antibody that targets beta-amyloid clusters in mild AD. Recent advancement in therapy, lecanemab, a recombinant IgG1 monoclonal antibody is targeted against aggregated soluble and insoluble forms of amyloid beta, thereby minimizing Aβ plaques and preventing Aβ deposition in the brain. As research advances, molecular basis of disease becomes more apparent leading to the advent of plausible targeted therapy.